Novel pathogenic GCH1 variant in familial Dopa-responsive dystonia - Engel, Johanna Marie; Dzinovic, Ivana; Zech, Michael; Janzarik, Wibke Gesine (Neuropediatrics)
Two adolescent female patients, who were referred independently of each other, presented with progressive gait disturbances that worsened over the course of the day. Symptoms began in early childhood with foot instability and progressed to clubfoot, pain, and limping. MRI of the neuroaxis did not reveal any central nervous system abnormalities. Genetic testing identified the same intronic variant of uncertain significance in GCH1 in both individuals. Subsequent investigations uncovered a previously unrecognized familial relationship between the two patients, belonging to an extended family in which six women were affected by a gait disorder. Previous diagnoses within the family included childhood-onset spasticity and psoriatic arthritis. The familial GCH1 variant was confirmed in all symptomatic individuals, as well as in two asymptomatic female carriers. RNA sequencing revealed a splicing defect caused by the GCH1 near splice-site variant. A robust clinical response to L-Dopa therapy confirmed the diagnosis of dopa-responsive dystonia (DRD) in this family. This case highlights the phenotypic variability of DRD, which frequently leads to misdiagnosis and delays in appropriate treatment. Careful assessment of family history and recognition of diurnal symptom fluctuations are key to identifying this highly treatable condition.